Measuring competitiveness - Neary, J. Peter (IMF working paper ;, 2006)
This paper reviews alternative approaches to measuring an economy's cost competitiveness and proposes some new measures inspired by the economic theory of index numbers. The indices provide a theoretical benchmark for estimated real effective exchange rates, but differ from standard measures in that they are based on marginal rather than average sectoral shares in GDP or employment. The use of the new indices is illustrated by some simple calculations that highlight the potential exposure of the Irish economy to fluctuations in the euro-sterling exchange rate.